PENGARUH KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI ENI MUARA BAKAU BV - Joey Rivaldo Simanjuntak; Herold Moody Manalu (Fakultas Ekonomi Universitas Advent Indonesia, 2022)
The purpose of this study was to determine the impact of taxpayer awareness of individual tax compliance at ENI Muara Bakau BV. Participants in this survey were employees working at Eni Muara Bakau BV. The survey method used in this survey was to distribute the survey to respondents who met the sample selection criteria. The data analysis used a variety of validity and reliability tests, descriptive statistical tests, classical hypothesis tests, simple linear regression tests, T and F hypothesis tests, and certainty tests. The number of valid samples in this survey was 100 respondents. The investigation revealed that the level of taxpayer awareness has a significant impact on the level of compliance of each taxpayer at Eni Muara Bakau BV.